Translocalities/Translocalidades Feminist Politics of Translation in the Latin/a Américas - Agustín, Lao-Montes; Alvarez, Sonia E.; Ana Rebeca, Prada; Claudia De Lima, Costa; Costa, Claudia de Lima; Ester R., Shapiro; Feliu, Veronica; Hester, Rebecca; Isabel, Espinal; Kiran, Asher; Klahn, Norma; Macarena, Gómez-Barris; et al. (Duke University Press, 2014)
Translocalities/Translocalidades is a path-breaking collection of essays on Latin American, Caribbean, and United States-based Latina feminisms and their multiple translations and cross-pollinations. The contributors come from countries throughout the Américas and are based in diverse disciplines, including media studies, literature, Chicana/o studies, and political science. Together, they advocate a hemispheric politics based on the knowledge that today, many sorts of Latin/o-americanidades-Afro, queer, indigenous, feminist, and so on-are constructed through processes of translocation. Latinidad in the South, North and Caribbean "middle" of the Américas, is constituted out of the intersections of the intensified cross-border, transcultural, and translocal flows that characterize contemporary transmigration throughout the hemisphere, from La Paz to Buenos Aires to Chicago and back again. Rather than immigrating and assimilating, many people in the Latin/a Américas increasingly move back and forth between localities, between historically situated and culturally specific, though increasingly porous, places, across multiple borders, and not just between nations. The contributors deem these multidirectional crossings and movements, and the positionalities engendered, translocalities/translocalidades.Contributors. Sonia E. Alvarez, Kiran Asher, Victoria (Vicky) M. Bañales, Marisa Belausteguigoitia Rius, Maylei Blackwell, Cruz C. Bueno, Pascha Bueno-Hansen, Mirangela Buggs, Teresa Carrillo, Claudia de Lima Costa, Isabel Espinal, Verónica Feliu, Macarena Gómez-Barris, Rebecca J. Hester, Norma Klahn, Agustín Lao-Montes, Suzana Maia, Márgara Millán, Adriana Piscitelli, Ana Rebeca Prada, Ester R. Shapiro, Simone Pereira Schmidt, Millie Thayer